Correction: Polyaniline nanorods dotted on graphene oxide nanosheets as a novel super adsorbent for Cr(vi). Issue 1 (8th December 2022) - Zhang, Shouwei; Zeng, Meiyi; Xu, Wenqing; Li, Jiaxing; Li, Jie; Xu, Jinzhang; Wang, Xiangke
Abstract : Correction for 'Polyaniline nanorods dotted on graphene oxide nanosheets as a novel super adsorbent for Cr(vi )' by Shouwei Zhang et al., Dalton Trans., 2013, 42, 7854–7858, ; https://doi.org/10.1039/C3DT50149C .